Islamic Securities Crowdfunding (I-SCF): A Potential Analysis of Sustainable Development Goals Based on Al-Maqashid Sharias Perspectives - Wafa, Fadhila Dhiyaul; Cahyanti, Irni Sri; Muhsin, Muhsin (Journal of Accounting Research, Organization and Economics, 2022)
Objective This research aims to analyze the potential of Islamic securities crowdfunding as an effort to create Sustainable Development Goals (SDGs) with an al-Maqashid Sharia perspective.Methodology This research uses qualitative descriptive research methods to obtain a description or overview of the potential of I-SCF for the Sustainable Development Goals based on the perspective of Maqashid Sharia. It utilizes a literature study with a Maqashid Sharia perspective as the main reference.Results Numerous studies show that sharia securities crowdfunding has the potential to strengthen MSME capital in the post-Covid-19 pandemic era, expand access to Islamic financial services for the community, create a profitable investment sector, and strengthen the halal industry. These potentials lead to the values of the purpose of Maqashid Sharia, which include the five main benefits (al-kulliyah al-khamsah).Research limitations This research is limited to I-SCF in Indonesia hence subsequent studies may conduct further research on I-SCF in other countries for the purpose of comparisons. It also uses a quality-descriptive method hence future research may use quantitative analysis methods to provide a more specific picture of the influence on the SDGs.Implications - This research is important for the development and utilization of the potential of I-SCF in Indonesia. The study of Maqashid sharia on I-SCF shows that practically, I-SCF has maximum benefits for society without abandoning compliance with Islamic law.